2017
DOI: 10.1590/1679-78253500
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Response of Dam-Reservoir Systems: Review and a Semi-Analytical Proposal

Abstract: This paper presents a review of current techniques employed for dynamic analysis of concrete gravity dams under seismic action. Traditional procedures applied in design bureaus, such as the Pseudo-Static method, often neglect structural dynamic properties, as well as ground amplification effects. A practical alternative arises with the Pseudo-Dynamic method, which considers a simplified spectrum response in the fundamental mode. The authors propose a self-contained development and detailed examples of this lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…ey compared the results of 8-node and 21-node elements and showed that the accuracy of the finite element model with 21-node element is higher. Ribeiro and Pedroso provided a review on the analysis method for concrete gravity dams under the effect of seismic load [10]. ey studied the limits of the previous methods by the finite element method and extracted the dam response using the semistatic, semidynamic and dynamic methods.…”
Section: Introductionmentioning
confidence: 99%
“…ey compared the results of 8-node and 21-node elements and showed that the accuracy of the finite element model with 21-node element is higher. Ribeiro and Pedroso provided a review on the analysis method for concrete gravity dams under the effect of seismic load [10]. ey studied the limits of the previous methods by the finite element method and extracted the dam response using the semistatic, semidynamic and dynamic methods.…”
Section: Introductionmentioning
confidence: 99%
“…Chopra [4] observed that the response of a dam when subjected to seismic loads was largely influenced by the fundamental mode of vibration, i.e., both the inertial and hydrodynamic forces depended on the fundamental mode of the structure vibration. Subsequently, Chopra and Chakrabarti [5], Hall and Chopra [6], Fenves and Chopra [7], Chopra and Zhang [8] and Ribeiro and Pedroso [9] evaluated other aspects that influenced the dam response under dynamic excitation, namely: fluid compressibility, fundamental vibration mode, foundation flexibility, as well as vertical and horizontal components of the earthquake. With the advancement of these studies and from the understanding of the problems involved, the researchers began to evaluate more complex geometries and problems, which mainly comprised the dam -reservoirfoundation coupled system.…”
Section: Introductionmentioning
confidence: 99%